Carbon Dioxide Chemically Responsive Switchable Gas Valves with Protonation‐Induced Liquid Gating Self‐Adaptive Systems. (28th February 2022) - Lei, Jinmei; Hou, Yaqi; Wang, Huimeng; Fan, Yi; Zhang, Yunmao; Chen, Baiyi; Yu, Shijie; Hou, Xu
Abstract: Carbon dioxide (CO2 ) capture and storage technologies are promising to limit CO2 emission from anthropogenic activities, to achieve carbon neutrality goals. CO2 capture requires one to separate CO2 from other gases, and therefore a gas flow system that exhibits discernible gating behaviors for CO2 would be very useful. Here we propose a self‐adaptive CO2 gas valve composed of chemically responsive liquid gating systems. The transmembrane critical pressures of the liquid gate vary upon the presence of CO2, due to the superamphiphiles assembled by poly(propylene glycol) bis(2‐aminopropyl ether) and oleic acid in gating liquids that are protonated specifically by CO2 . It is shown that the valve can perform self‐adaptive regulation for specific gases and different concentrations of CO2 . This protonation‐induced liquid gating mechanism opens a potential platform for applications of CO2 separators, detectors, sensors and beyond. Abstract : A self‐adaptive CO2 gas valve composed of chemically responsive liquid gating systems is reported, and the transmembrane critical pressures of the liquid gate vary upon the presence of CO2, due to the superamphiphiles assembled by poly(propylene glycol) bis(2‐aminopropyl ether) and oleic acid in gating liquids that are protonated specifically by CO2 .